Complex post-traumatic elbow stiffness: Nonunion, malunion, and post-traumatic arthritis (2016)
A flexion contracture is the most common complication after elbow trauma. Several theories and risk factors have been associated with this entity. Soft tissues, osteoarthritic changes, capsule, and bone may be involved in post-traumatic stiffness. A thorough history, physical examination, and appropriate imaging assist with diagnosis and management. Various surgical and nonsurgical treatment options exist in the management of nonunion, malunion, and osteoarthritis after traumatic injury. Management decisions must take into account the functional status and expectations of the patient as well as the surgeon's level of expertise. © 2016 Elsevier Ltd All rights reserved.